Mycobacterium tuberculosis Transmission between Cluster Members with Similar Fingerprint Patterns - Kashef Ijaz; Zhenhua Yang; H. Stewart Matthews; Joseph H. Bates; M. Donald Cave (Emerging Infectious Diseases, 2002)
Molecular epidemiologic studies provide evidence of transmission of Mycobacterium tuberculosis within clusters of patients whose isolates share identical IS6110-DNA fingerprint patterns. However, M. tuberculosis transmission among patients whose isolates have similar but not identical DNA fingerprint patterns (i.e., differing by a single band) has not been well documented. We used DNA fingerprinting, combined with conventional epidemiology, to show unsuspected patterns of tuberculosis transmission associated with three public bars in the same city. Among clustered TB cases, DNA fingerprinting analysis of isolates with similar and identical fingerprints helped us discover epidemiologic links missed during routine tuberculosis contact investigations.